Święty Jan z Ávili doktorem Kościoła - Wojciech Zyzak (Polonia Sacra)
The Author of the article shows the life and meaning of Saint John of Ávila, announced by Pope Benedict XVI a new Doctor of the Church on 7 October 2012. The text presents his holy life, his works and his eminent doctrine. The author characterizes the works of the saint, especially the tractate Audi, filia. He also presents the most important ideas of his teaching: Christology, the concept of the Church, the cardinal virtues, especially the faith, the theory of prayer, asceticism, mystic and the development of spiritual life. He also shows John of Ávila as an expert in priestly spirituality.